3D cardiac magnetic resonance stress-perfusion in elderly patients. (13th July 2021) - Karolyi, M; Gotschy, A; Plein, S; Paetsch, I; Jahnke, C; Frick, M; Gebker, R; Alkadhi, H; Manka, R
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Swiss National Science Foundation Introduction: Age related comorbidities and reduced compliance often limit ischaemia testing in elderly patients. Purpose: To assessed the accuracy of 3D cardiac magnetic resonance (CMR) stress perfusion in the elderly population. Methods: 56 patients aged ≥75 years underwent 3D CMR stress-perfusion and invasive coronary angiography with quantitative coronary angiography (QCA) and fractional flow reserve (FFR) as part of a multicenter study. The accuracy of 3D CMR stress-perfusion was compared to patients aged <75 years old (n = 360) using qualitative and quantitative imaging parameters. Results: Sensitivity, specificity, positive and negative predictive values of qualitative 3D perfusion CMR were similar for both age groups in the detection of high-grade (≥50%) coronary stenosis on QCA and hemodynamically relevant (<0.8) stenosis on FFR, p > 0.05 all. Quantitative myocardial ischemia burden was larger in elderly patients (15% ± 17% vs. 9% ± 13%) with similarly high diagnostic accuracy of quantitative 3D CMR perfusion in both age groups to predict pathological FFR (AUC ≥75: 0.906; AUC <75: 0.866). Conclusions: 3D CMR perfusion is well suited for myocardial ischaemia testing in the elderly patients with similarly high diagnostic accuracy as in younger individuals.